Revisiting treatment-related cardiotoxicity in patients with malignant lymphoma—a review and prospects for the future - Rihackova, Eva; Rihacek, Michal; Vyskocilova, Maria; Valik, Dalibor; Elbl, Lubomir (Frontiers in Cardiovascular Medicine, 2023)
Treatment of malignant lymphoma has for years been represented by many cardiotoxic agents especially anthracyclines, cyclophosphamide, and thoracic irradiation. Although they are in clinical practice for decades, the precise mechanism of cardiotoxicity and effective prevention is still part of the research. At this article we discuss most routinely used anti-cancer drugs in chemotherapeutic regiments for malignant lymphoma with the focus on novel insight on molecular mechanisms of cardiotoxicity. Understanding toxicity at molecular levels may unveil possible targets of cardioprotective supportive therapy or optimization of current therapeutic protocols. Additionally, we review novel specific targeted therapy and its challenges in cardio-oncology.